2012
DOI: 10.1136/bmj.e2359
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Talking Diabetes consulting skills intervention on glycaemic control and quality of life in children with type 1 diabetes: cluster randomised controlled trial (DEPICTED study)

Abstract: Objective To evaluate the effectiveness on glycaemic control of a training programme in consultation skills for paediatric diabetes teams.Design Pragmatic cluster randomised controlled trial.Setting 26 UK secondary and tertiary care paediatric diabetes services.Participants 79 healthcare practitioners (13 teams) trained in the intervention (359 young people with type 1 diabetes aged 4-15 years and their main carers) and 13 teams allocated to the control group (334 children and their main carers).Intervention T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 37 publications
6
88
1
Order By: Relevance
“…Those studies confirmed that higher level of support is significantly influencing the blood glucose monitoring at home (13,14,17,20,24,34) . For medication taking behavior, seven studies demonstrated that regularly medication adherence was conducted under the family support (14,15,(18)(19)(20)(21) .…”
Section: Self-care Behavior Outcomessupporting
confidence: 65%
See 4 more Smart Citations
“…Those studies confirmed that higher level of support is significantly influencing the blood glucose monitoring at home (13,14,17,20,24,34) . For medication taking behavior, seven studies demonstrated that regularly medication adherence was conducted under the family support (14,15,(18)(19)(20)(21) .…”
Section: Self-care Behavior Outcomessupporting
confidence: 65%
“…This review verified that five studies follow-up the program by using a face-to-face follow-up (12,15,17,(22)(23)(24)33) . Three studies were noticed to follow-up the program by using the telephone method (13,14,25,26,32) .…”
Section: Follow-up Strategiesmentioning
confidence: 91%
See 3 more Smart Citations